Why the Protestors are AgainstCorporate Globalization - McMurtry, John (Journal of business ethics, 2002)
It is generally believed by governing political parties, economists, business people and other believers in global market doctrine that those who oppose "free trade agreements" are misled, uninformed and "do not really know what they are protesting against". At the same time, the opponents of these transnational trade-and-investment restructurings have diverse concerns ranging from loss of democratic sovereignty, labour rights and environmental protection of majority-world oppression, the growth of poverty and inequality, and global cultural homogenization. The following analysis integrates the growing multitude of critical attacks on these extra-parliamentary agreements into a systematic anatomy of the latter's underlying structure whose regulating principles are not yet recognised or debated in business, political or economic circles.